Effect of the heat transfer liquid fin on critical heat flux enhancement under ERVC condition. (April 2020) - Lee, Min Ho; Heo, Hyo; Bang, In Cheol
Highlights: The heat transfer liquid fin concept was suggested to address the issue of CHF in IVR-ERVC for its selective applicability in accident situations. Conduction and natural circulation were the dominant heat transfer mechanisms in the case of liquid metal fin and the oil fin, respectively. Regardless of the properties of the fin, it can provide additional margin for CHF by mitigation of the localized heat flux. Abstract: Several critical heat flux (CHF) enhancement methods for in-vessel retention through external reactor vessel cooling (IVR-ERVC) have been researched. However, they have some limitations for practical applications. In the present study, heat transfer liquid fin concept was suggested to address the issue of CHF by spreading focusing effect of the heat flux. The liquid fin was located outside of the reactor pressure vessel; it is activated by filling under the accident situations. Liquid metal and oil were selected as the fin materials as they are characterized by significantly different Prandtl numbers; this property helps to clearly distinguish the heat transfer mechanisms involved. Analysis were conducted based on both experimental and numerical methods. As expected, conduction and natural circulation were the dominant heat transfer mechanisms in the case of liquid metal fin and the oil fin, respectively. Regardless of the Prandtl number of the fin, safety margin for the CHF was significantly increased in both fin cases. The heat flux profile of the conduction dominant liquid metal fin showed a moderately flattened shaped. However, for the oil fin, heat flux was mitigated and upwardly shifted (natural circulation as the primary heat transfer mechanism). Although both materials exhibited good performance in terms of securing a margin for CHF, temperature increment by the liquid fin was much higher in the oil case because of the relative lower thermal conductivity of the latter. Thus, the use of low thermal conductivity fins requires the temperature limit to be taken into consideration.